Effective light beam modulation by chirp IDT on a suspended LiNbO3 membrane for 3D holographic displays - Lee, Yongbeom; Lee, Keekeun (Sensors (Switzerland), 2020)
An acousto-optic (AO) holographic display unit based on a suspended waveguide membrane was developed. The AO unit consists of a wide bandwidth chirp interdigital transducer (IDT) on a 20 µm thick suspended crystalline 128◦ YX LiNbO3 membrane, a light blocker with a 20 µm hole near the entrance, and an active lens near the exit. The 20 µm thickness of the floating membrane significantly enhanced surface acoustic wave (SAW) confinement. The light blocker was installed in front of the AO unit to enhance the coupling efficiency of the incident light to the waveguide membrane and to remove perturbations to the photodetector during measurement at the exit region. The active lens was vertically attached to the waveguide sidewall to collect the diffracted beam without loss and to modulate the focal length in free space through the applied voltage. As SAWs were radiated from the IDT, a Bragg grating with periodic refractive indexes was formed along the waveguide membrane. The grating diffracted incident light. The deflection angle and phase, and the intensity of the light beam were controlled by the SAW frequency and input power, respectively. The maximum diffraction efficiency achieved was approximately 90% for a 400 MHz SAW. COMSOL simulation and coupling of mode modeling were performed to optimize design parameters and predict device performance.
Keywords: 3D holographic displays; Bragg diffraction; Coupling efficiency; Coupling of modes; Deflection angles; Device performance; Interdigital transducer; Surface acoustic waves; Acousto-optic; Active lens; Bragg diffraction; Holographic display; Surface acoustic wave; Waveguide